Microsoft office project 2007 inside out - Stover, Teresa S. (Microsoft Press, 2007)
Learn everything you need to know for working with Microsoft Office Project 2007. This book packs hundreds of time-saving solutions, troubleshooting tips, and workarounds for using Office Project 2007. Whether youre a project manager or just working to meet your deadlines, youll be able to dig in to the work-ready resources that help you plan, manage, and communicate project information more effectively. Youll learn how to develop a project plan; orchestrate project scope, resources, and time; track your progress; collaborate with others; and report and analyze all your project information. You'll also learn how to manage and participate in projects with Office Project 2007's enterprise project management capabilities. You'll even learn how to administer users and enterprise resource pools in Project Server 2007.